The Influence Of Work Motivation, Organizational Commitment And Work Environment On Village Apparatus Performance In South Seluma Sub-District - Sri Astuti; Ahmad Soleh; Ermy Wijaya (Penerbit Jurnal Indonesia, 2024)
The level of village apparatus performance is still low because village apparatus lack high motivation in working, this can be seen from the lack of initiative from village apparatus to do something new or provide new ideas so that they can improve performance. The aim of this research is to determine the influence of work motivation, organizational commitment and work environment on village apparatus performance in South Seluma Sub-District. The sample in this study was 72 village apparatus in South Seluma Sub-District. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the multiple regression test show a positive direction with the regression equation Y = 1.330 + 0.253X1 + 0.315 X2 + 0.399X3. Variable X1 (Motivation) has a significant effect on Y (performance). This can be seen from the significance value of 0.001 < 0.05, so it can be concluded that hypothesis 1 is accepted. The variable X2 (organizational commitment) has a significant effect on Y (performance). This can be seen from the significance value of 0.000 < 0.05. Then it can be concluded that hypothesis 2 is accepted. Variable X3 (work environment) has a significant effect on Y (performance). This can be seen from the significant value of 0.000 < 0.05, so it can be concluded that hypothesis 3 is accepted. Simultaneous test results show that H0 is rejected and Ha is accepted, the independent variables, namely X1 (motivation), X2 (organizational commitment), X3 (work environment), have a significant influence together on performance (Y) because the significant value is 0.000 is smaller than 0.05